Taking Time: A Mixed Methods Study of Parkinson’s Disease Caregiver Participation in Activities in Relation to Their Wellbeing - Lia Prado; Rebecca Hadley; Dawn Rose (Parkinson's Disease)
Objectives. Although many studies have shown that psychosocial interventions, such as dance classes, can improve quality of life for people with Parkinson’s disease (PD): few have addressed the role of, and potential benefits to, the caregivers in such activities. This mixed methods study explored the reasons for caregiver participation in a variety of activities and considered whether participation in, or abstention from these, affected the wellbeing of the caregivers. Method. Transcriptions of a focus group (two people with PD, two caregivers) and eight semistructured interviews (caregivers) were analysed using Grounded Theory (GT). To test the hypotheses derived from the GT, caregivers (n = 75) completed an online survey about activities they and the person they care for participated in, alongside the PDQ-Carer questionnaire, to establish the caregiver’s levels of wellbeing. Results. Qualitative findings suggested that caregivers tried to find a balance between caring for the person with PD and participating in activities to attend to their own needs. Reasons for participating in activities for people with PD included being able to socialise in an empathetic safe space, alongside engaging in physical activity that provided some respite distraction, such as dancing with others to music. Reasons for not participating included generating time for oneself and increasing the independence of the person with PD. Quantitative results suggested that most of the participants’ wellbeing was not compromised, although this was gendered: female caregivers reported lower wellbeing scores than male caregivers. Overall, 62% of caregivers participated in joint activities. Linear regression revealed a significant relationship between nonparticipation in daily activities and stress levels for female caregivers only, whereby the more independent the person with PD was, the lower the stress of the caregiver. Conclusion. This study suggests that caregivers of people with PD can find a healthy balance in terms of their own wellbeing by jointly participating in two-thirds of activities while ensuring the remaining third is time reserved for themselves.